Italian Clinical Practice Guidelines on Cholangiocarcinoma – Part I: Classification, diagnosis and staging - Alvaro, Domenico; Hassan, Cesare; Cardinale, Vincenzo; Carpino, Guido; Fabris, Luca; Gringeri, Enrico; Granata, Vincenza; Mutignani, Massimiliano; Morement, Helen; Giuliante, Felice; Guglielmi, Alfredo; Ridola, Lorenzo; et al. (Digestive and liver disease, 2020)
Cholangiocarcinoma (CCA) is the second most common primary liver cancer, characterized by a poor prognosis and resistance to chemotherapeutics. The progressive increase in CCA incidence and mortality registered worldwide in the last two decades and the need to clarify various aspects of clinical management have prompted the Italian Association for the Study of the Liver (AISF) to commission the drafting of dedicated guidelines in collaboration with a group of Italian scientific societies. These guidelines have been formulated in accordance with the Italian National Institute of Health indications and developed by following the GRADE method and related advancements.